Virus Infection and Blood Coagulation - Gagel, Ch; Linder, M; Müller-Berghaus, G; Lasch, H. G (Thrombosis and Haemostasis, 1970)
By means of a new model, the fowl plague of chickens, further evidence is given that viruses may trigger blood coagulation. Macroscopically, hemorrhages were observed, whereas microscopic studies revealed platelet and fibrin thrombi in the small vessels of various organs. Hematologic studies demonstrated an increase in the clotting time and a decrease in the activities of clotting factors I, II, VIII and X, and drop in platelet counts. Heparin could diminish the hemorrhages but did not influence the survival time of the animals.